Accipiter cooperi - James, Helen F. (Zenodo, 2020)
Accipiter cooperi Material. USNM PAL 641980, l coracoid: dorsal one-third, collected October 8, 1999. Description. The bone falls in the size range of large males and small females of modern A. cooperi . I compared it with modern species of North American Accipitriformes in roughly the same size class. The fossil is much more slender and less pneumatic than in Elanoides forficatus or Rostrhamus sociabilis . The pneumatic foramen in the sulcus m. supracoracoidei is smaller and the acrocoracoid process is less inflated than in Circus cyaneus . The fossil resembles A. cooperi as opposed to Buteo lineatus and B. platypterus in having a relatively slender facies articularis humeralis (glenoid facet) and a less extended procoracoid process. Remarks. This species still occurs in the region of the cave. It was previously reported from other Irvingtonian fossil localities and from a late Blancan locality in Florida (Emslie 1998). Published as part of James, Helen F., 2020, The Irvingtonian Avifauna of Cumberland Bone Cave, Maryland, pp. 111-131 in Zootaxa 4772 (1) on page 120, DOI:10.11646/zootaxa.4772.1.4, http://zenodo.org/record/3814013